Family Matters: Rethinking the Psychology of Human Social Motivation - Ko, Ahra; Pick, Cari M; Kwon, Jung Yul; Barlev, Michael; Krems, Jaimie Arona; Varnum, Michael E W; Neel, Rebecca; Peysha, Mark; Boonyasiriwat, Watcharaporn; Brandstätter, Eduard; Crispim, Ana Carla; Cruz, Julio Eduardo; et al. (Perspectives on psychological science, 2020)
What motives do people prioritize in their social lives? Historically, social psychologists, especially those adopting an evolutionary perspective, have devoted a great deal of research attention to sexual attraction and romantic-partner choice (mate seeking). Research on long-term familial bonds (mate retention and kin care) has been less thoroughly connected to relevant comparative and evolutionary work on other species, and in the case of kin care, these bonds have been less well researched. Examining varied sources of data from 27 societies around the world, we found that people generally view familial motives as primary in importance and mate-seeking motives as relatively low in importance. Compared with other groups, college students, single people, and men place relatively higher emphasis on mate seeking, but even those samples rated kin-care motives as more important. Furthermore, motives linked to long-term familial bonds are positively associated with psychological well-being, but mate-seeking motives are associated with anxiety and depression. We address theoretical and empirical reasons why there has been extensive research on mate seeking and why people prioritize goals related to long-term familial bonds over mating goals. Reallocating relatively greater research effort toward long-term familial relationships would likely yield many interesting new findings relevant to everyday people's highest social priorities.
Keywords: Social Behavior; Humans; Sexual Behavior; lidé středního věku; evolutionary psychology; interpersonální vztahy; Female; Cross-Cultural Comparison; mladý dospělý; dospělí; srovnání kultur; Family Relations; sociální chování; Goals; lidé; motivation; family; reward; Adult; ženské pohlaví; Male; Middle Aged; interpersonal relations; Young Adult; rodinné vztahy; cíle; goals; mužské pohlaví; Reward; Interpersonal Relations; odměna; sexuální chování